2014
DOI: 10.1038/ng.3016
|View full text |Cite
|
Sign up to set email alerts
|

A specific missense mutation in GTF2I occurs at high frequency in thymic epithelial tumors

Abstract: We analyzed 28 thymic epithelial tumors (TETs) using next-generation sequencing and identified a missense mutation (chromosome 7 c.74146970T>A) in GTF2I at high frequency in type A thymomas, a relatively indolent subtype. In a series of 274 TETs, we detected the GTF2I mutation in 82% of type A and 74% of type AB thymomas but rarely in the aggressive subtypes, where recurrent mutations of known cancer genes have been identified. Therefore, GTF2I mutation correlated with better survival. GTF2I β and δ isoforms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
297
8
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(335 citation statements)
references
References 44 publications
18
297
8
3
Order By: Relevance
“…S6B). Recently, it has been shown that cancer-specific mutations of TFII-I increase cell proliferation (46). Though it remains to be proven, it is also possible that loss of function GTF2i mutations may disrupt metabolic homeostasis to provide a survival advantage that is distinct from its previously described role in proliferation (47,48).…”
Section: Resultsmentioning
confidence: 99%
“…S6B). Recently, it has been shown that cancer-specific mutations of TFII-I increase cell proliferation (46). Though it remains to be proven, it is also possible that loss of function GTF2i mutations may disrupt metabolic homeostasis to provide a survival advantage that is distinct from its previously described role in proliferation (47,48).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, GTF2I missense mutations have been found in types A and AB thymomas and less commonly in types B1, B2, and B3 thymomas. 64 These mutations were rather uncommon in thymic carcinoma (Table 9).…”
Section: Genetic Alterations In Thymic Epithelial Tumorsmentioning
confidence: 99%
“…50 % der Fälle AIRE(+)-Epithelzellen und Desmin(+)-Myoidzellen nachweisbar sind. Genetische Alterationen sind seltener als in B2-und B3-Thymomen [7,18], GTF2I-Mutationen kommen in 32 % der Fälle vor [21].…”
Section: Prognoseunclassified
“…Genetische Alterationen sind seltener als in B3-Thymomen, überlappt aber bei Verlusten von 6q25,2-q25,3 und 3p und Zugewinnen von 1q [7,18]. Zweiundzwanzig Prozent zeigen GTF2I-Mutationen [21]. T-LBL weisen auch TdT(+), aber atypische Lymphoblasten auf, die das Keratin(+)-thymische Epithelzellnetz destru-Abb.…”
Section: )unclassified
See 1 more Smart Citation